Stormwater Reuse Project Provides Lessons in Cooperation. Issue 9 (1st September 2013) - Wittig, James; Mack, Brian; Williams, Jane
Abstract : The city of Orlando, Fla., and the Florida Department of Transportation joined forces to accomplish cost‐effective stormwater control, treatment, and reuse goals.